Pengaruh Brand Ambassador, Sales Promotion, Social Media Marketing, Perilaku Konsumtif, Brand Trust, dan Label Halal terhadap Keputusan Pembelian - Anggi Fitri Elisah; Nova Anggrainie (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The dairy industry seeks to increase consumption through various marketing strategies, because from BPS data in 2020, the level of milk consumption in Indonesia is still low. The aim of this investigation was to analyze the impact of brand ambassadors, sales promotion, social media marketing, consumptive behavior, brand trust, also halal labels on purchasing decisions for Ultra Milk x ITZY products. This investigation uses a quantitative approach with a questionnaire instrument filled out by 245 respondents, where the data is analyzed using normality, heteroscedasticity, multicollinearity, validity, reliability, also multiple linear regression analysis tests. The outcome showed that all independent variables, namely the impact of brand ambassadors, sales promotion, social media marketing, consumptive behavior, brand trust, also halal labels had a significant impact on purchasing decisions both partially also simultaneously. Overall, these variables influence purchasing decisions by 92.4%. This study concludes that these marketing factors play an crucial role in impacting consumer decisions to buy dairy products, also can be used as a reference to improve marketing strategies in an effort to increase milk consumption in Indonesia.